The Precautionary Principle and the Technical Environmental Evaluation: The Case of Fipronil and the Death of Bees in Colombia - Luna-Galván, Mauricio; Vargas-Chaves, Iván; Permana, Yogi Setya (Fronteira: Journal of Social, Technological and Environmental Science, 2024)
The increasing use of pesticides for agricultural use attempts to enhance food security and improve crop production, however there is a growing debate on the arising problems for producing food, the loss of biodiversity and harvesting practices under the use of pesticides agrochemicals. This article analyzes the use of FIPRONIL and the death of bees in the case of Colombia, by integrating the precautionary principle with the international law and national legal-environmental frameworks with the approach of human security and food security which are pertinent and relevant under the increasing use of chemical pesticides for agricultural use, and also seeks to establish criteria and proceedings of the technical environmental evaluation that can be applied in the country. The article argues that the precautionary principle and measures are key to control and prevent hazardous and potential risks in human health and food security from agricultural production, and finally recommends strengthening the approach of food security and to raise the conceptual aspects of food security once again, especially instability, use, and availability of food that should be included in national and international law.